Addressing Ceremonious Compliance and Problematic Agency-Level Hate Crime Reporting: Charting Progress, Promises, and Policy Possibilities - Vanden Bosch, Matthew (Criminal justice policy review, 2026)
Research in both criminology and sociology has emphasized the problem of organizational compliance with legal mandates, including law enforcement compliance. Recent research has drawn attention to the problem of police agency use of purely symbolic structures (ceremonious compliance) that appear to comply with legal mandates, while their practices reject the underlying ideals—most notably with regard to hate crime data reporting. The present work describes the current status of federal legislation regarding hate crimes and data collection, including signed legislation as well as introduced bills not yet subjected to a vote. In addition to describing the current socio-legal landscape surrounding hate crime data collection, we also discuss promising aspects of recent legislation, weaknesses, and potential changes that could be made to enhance the accuracy of hate crime data. Our results reveal how legislation shapes law enforcement hate crime reporting and how organizations respond to legal mandates more broadly.